The Inspection like quality factor in the educational system - Oliver Pozo, Joaquín (Avances en Supervisión Educativa, 2016)
The Inspection, along with other educational sectors, shapes from complementarity, coordination and communication between them, the architecture of the educational system. Each has its specificity and its own space in Education. The aim of this study is simply identify and define the location of the inspection into the education system, between educational administration and schools, and the "why" (their mission), and consistent with it, "which makes" (its functions and assignations). Mission and functions that take place in schools, at the sight of the Educational Administration and the society, through the Inspectorate as organization. Of the principles underlying this organization and of the communication, training, and technical and professional exchange that drives through their organizational structures, will depend its leadership in Education and to be seen as a quality factor.
Keywords: aim of the inspection; functions; competence assignment; the inspectorate like organization; specialization; teamwork